App-based daily self-measurement of impedance in cochlear implant users - Vormelcher, Sarah; Batsoulis, Cornelia; Kley, Daniel; Mair, Michael; Büchner, Andreas (Frontiers in Neurology, 2025)
IntroductionImpedance telemetry measurements in cochlear implant (CI) recipients are commonly used to assess CI electrode functionality and provide valuable insights into inner ear conditions. However, these measurements usually take place only during surgery and at clinical follow-up appointments, offering limited temporal resolution of impedance changes. This study aimed to address this gap by implementing daily impedance monitoring using a smartphone app.MethodsA prospective study evaluated the usability of a research app for remote impedance measurements over 4 months following standard CI surgery with a MED-EL FLEX28 electrode. Impedance was recorded twice daily (morning and evening). The mean impedance across all electrode channels was analyzed for four postoperative time periods: early postoperative (up to day 10 postoperatively), late postoperative (from day 11 to ~4 weeks), intensive fitting (from ~4 weeks postoperatively to ~7 weeks) and regular hearing phase (from ~7 weeks to 4 months). Two CI fitting approaches were compared: activation during the early postoperative phase (early activation, EA) and activation during the intensive fitting phase (conventional activation, CA). Morning-to-evening differences in impedance (MED) were also examined.ResultsThe app demonstrated an overall usage rate of 66% (n = 28), indicating moderate-to-high adherence. Except for higher evening impedance values with CA in the late postoperative phase, no significant differences in mean impedance between the fitting approaches were observed (EA: 6.46 kΩ, n = 11; CA: 7.82 kΩ, n = 11; p = 0.04). Significant differences in MED were found during the early postoperative phase (EA: 0.06 kΩ, n = 8; CA: −0.18 kΩ, n = 10; p = 0.04) and the late postoperative phases (EA: 0.85 kΩ, n = 11; CA: 0.03 kΩ, n = 11; p < 0.001).ConclusionRemote impedance measurements via the app can be made over an extended postoperative period. The increased measurement frequency allowed for detailed characterization of impedance dynamics, particularly around the onset of electrical stimulation. No clinically relevant difference in mean impedance was found between EA and CA groups. Daily fluctuations showed consistently lower evening values after stimulation onset. These findings highlight the potential value of this approach for enhancing postoperative CI management.